The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.resp.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory-swallowing coordination in normal subjects: Lung volume at swallowing initiation

Abstract: This study was designed to investigate the significance of bolus types and volumes, delivery methods and swallowing instructions on lung volume at swallowing initiation in normal subjects in a single experiment using a multifactorial approach. Our broad range goal was to determine optimal lung volume range associated with swallowing initiation to provide training targets for dysphagic patients with disordered respiratory-swallow coordination. Our hypothesis was that swallows would be initiated within a limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 63 publications
1
57
2
Order By: Relevance
“…Percentage of time the phase followed a swallow (%) cough reflex under the circumstances of a possible penetration/aspiration in large bolus volume. This inference is supported by earlier reports of Hegland, Huber, Pitts, and Sapienza (2009) and McFarland, Martin-Harris, Fortin, Humphries, Hill, and Armeson (2016) that found higher lung volume at initiation of thin-liquid swallows [42,43]. This protective mechanism is operational irrespective of head position, as suggested by the findings of this study.…”
Section: Discussionsupporting
confidence: 91%
“…Percentage of time the phase followed a swallow (%) cough reflex under the circumstances of a possible penetration/aspiration in large bolus volume. This inference is supported by earlier reports of Hegland, Huber, Pitts, and Sapienza (2009) and McFarland, Martin-Harris, Fortin, Humphries, Hill, and Armeson (2016) that found higher lung volume at initiation of thin-liquid swallows [42,43]. This protective mechanism is operational irrespective of head position, as suggested by the findings of this study.…”
Section: Discussionsupporting
confidence: 91%
“…As have been reported by others, an instruction of, “cough like there is something in your throat” produces a robust and reliable response [45]. Common for cued swallow is, have the participant hold the bolus in their mouth and swallow when prompted/ready [46], however McFarland, [18] demonstrated that cueing can have a significant effect on LV during swallow.…”
Section: Discussionmentioning
confidence: 93%
“…McFarland et al [14] found that swallows occur at a specific lung volume. Therefore, the humming maneuver might have made some subjects miss the optimal timing of swallowing.…”
Section: Humming Swallow Maneuvermentioning
confidence: 99%